A Blended Learning Experience in Statistics for Psychology Students Using the Evaluation as a Learning Tool - Alberto VALENTÍN CENTENO; M.ª del Mar GONZÁLEZ-TABLAS SASTRE; M.ª Estrella LÓPEZ PÉREZ; Pedro Manuel MATEOS GARCÍA (Ediciones Universidad de Salamanca, 2016)
Teaching statistics course Applied Psychology, was based on different teaching models that incorporate active teaching methodologies. In this experience have combined approaches that prioritize the use of ICT with other where evaluation becomes an element of learning. This has involved the use of virtual platforms to support teaching that facilitate learning and activities where no face-to-face are combined. The design of the components of the course is inspired by the dimensions proposed by Carless (2003) model. This model uses evaluation as a learning element. The development of this experience has shown how the didactic proposal has been positively interpreted by students. Students recognized that they had to learn and deeply understand the basic concepts of the subject, so that they can teach and assess their peers.